Blockchain-based technologies - María-Cruz Valiente; Florian Tschorsch (Internet Policy Review)
Blockchain-based technologies can be understood as a distributed network of computers, ideally organised in a decentralised way, mutually agreeing on a common state while tolerating failures (incl. malicious behaviour) to some extent.